(untitled) (Economics and region, 2025)
This article examines the theoretical-methodological and practical aspects of improving tax burden on small and medium enterprises (SMEs) in Ukraine under martial law conditions. The research addresses the critical importance of optimizing fiscal policy for SMEs, which constitute the backbone of Ukraine’s economy, representing 99.98% of all business entities, providing 74% of employment, and generating 64% of added value. The study analyzes the current state of tax regulation for SMEs, revealing significant variations in tax burden depending on the chosen taxation system. Statistical data demonstrates that average tax burden for entities operating under the general taxation system reaches 41.5% of added value, while for single tax payers it constitutes 27.3%. Sectoral analysis reveals substantial disparities: maximum rates are observed in financial services (46.2%), industrial production (44.7%), and construction (43.1%), while minimum rates characterize agriculture (22.8%), IT industry (25.4%), and retail trade (28.6%). The research methodology combines quantitative analysis of statistical data with assessment of international best practices. Special attention is given to the territorial distribution of tax burden, which shows concentration of highest rates in the capital region (43.2%), Dnipropetrovsk (42.1%), and Kharkiv (41.8%) oblasts, while the lowest rates are characteristic of Chernivtsi (32.4%), Ternopil (33.7%), and Zakarpattia (34.2%) oblasts. The study evaluates the effectiveness of government support programs implemented during the war, including the "5-7-9" lending program, grant initiatives, employment stimulation measures, and deregulation policies. Analysis reveals that only 49% of SMEs utilize available support instruments, indicating significant potential for improvement in accessibility and communication strategies. Key findings demonstrate that Ukrainian SMEs have shown remarkable resilience during the war, with 91% of enterprises resuming operations after the initial shock. However, challenges remain in optimizing tax burden to balance fiscal needs with business development stimulation. The article proposes strategic directions for improvement, including development of reliable digital tax administration infrastructure, implementation of inclusive digital platforms for taxpayer services, creation of transparent dispute resolution mechanisms, and establishment of adaptive tax burden systems that consider SME specifics in the context of digital economy transformation. The research concludes that successful tax policy reform requires building trust between the state and entrepreneurs through creation of an effective digital tax ecosystem that ensures transparency, speed, and security of tax operations while minimizing transaction costs and enhancing business confidence in the tax system.